Determinants of Volunteer Satisfaction in Non-Profit Organizations: The Role of Organizational Culture, Communication, and Transformational Leadership - Yakin, Ikram; Meutianingrum, Farah Juniati; Aprija, Een (Islamic University of Kalimantan MAB Banjarmasin, 2026)
The sustainability of Non-Profit Organization (NPO) is highly dependent on volunteer involvement, the strategic role of volunteers requires organizations to be able to implement a more strategic approach to retain volunteers while improving organizational performance. This study amidst to analyze the factors that significantly impact volunteer job satisfaction. Using quantitative methods of explanatory design through a survey approach to evaluate of organizational culture, transformational leadership on volunteer job satisfaction with communication as mediation. Population includes volunteers who work for non-profit organizations in West Kalimantan. Sample was taken with purposive sampling data was collected from 155 respondents. through the use of structured questionnaires and PLS-SEM analysis. The three variables have a partially significant positive relationship with the volunteer job satisfaction variable. Communication is able to fully mediate job satisfaction as well as being the most dominant variable compared to other variables. This shows that the success of non-profit organizations in maintaining the satisfaction and sustainability of volunteer involvement is largely determined by the effectiveness of the communication built, the large contribution of each variable in explaining variations in volunteer job satisfaction confirms that optimal volunteer management requires integration between a strong organizational culture, inspiring leadership, and open participatory communication.